Exemplary as a Method for Forming the Character Perspective of the Hadith of the Prophet Muhammad SAW - Abdurrahman; Sibawaihi; Akhmad Sholeh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Humans have a ghorizoh nature, namely the tendency to follow other people. So educators must provide examples in character formation so that students can follow them. This research aims to determine example as a character formation of the hadith perspective of the Prophet Muhammad SAW. This research is qualitative research using a library approach (library research) using books and other literature as the main data source. The data analysis technique uses the content analyzer method, which discusses in depth information obtained from written or printed media by comparing the contents of one document with other documents so that conclusions can be drawn. The results of this study show that exemplary is one of the methods that has proven effective in shaping character. As the Prophet Muhammad SAW used in conveying Islamic teachings so that they can be imitated by educators in shaping the character of students. This is because humans will be more able to accept something concrete than just conveying it verbally.